Asian multiculturalism in communication: Impact of culture in the practice of public relations in Singapore - YEO, Su Lin (Institutional Knowledge at Singapore Management University, 2017)
This study aims to understand the role of cultural values in influencing public relations practice in Singapore. Given that Singapore exhibits a hybrid of cultures, it purposes to comprehend how multiculturalism is operationalized and to uncover if the values that have a greater influence on organizational communication resemble those in individualistic or collectivistic societies. Using Gudykunst's (1998) seven dimensions that influence individualism-collectivism on communication as a guide, this study interviewed 20 public relations practitioners in Singapore. Our findings showed that although the patterns expressed is slightly more consistent with those found in collectivistic cultures, it does not resemble collectivism in entirety. Multiculturalism in Singapore displays a blend of certain cultural hybridity, which is aligned with it being a multicultural cosmopolitan city that embodies Western modernity while retaining its Asian values. Our findings further reinforced the idea that public relations professionals need to be multicultural themselves to effectively communicate with culturally diverse stakeholders in today's globalizing era of multiculturalism.